Suppressing parthenium weed with beneficial plants in Australian grasslands. Issue 2 (3rd April 2021) - Shabbir, Asad; Ali, Sadiq; Khan, Ijaz Ahmad; Belgeri, Amalia; Khan, Naeem; Adkins, Steve
Abstract: Parthenium hysterophorus is an alien invasive weed infesting grasslands in many countries around the world, including Australia. Previous studies have identified several native and introduced fodder species that can suppress biomass production of parthenium weed. In the present study, a total of 11 fodder species were tested for their ability to suppress growth of parthenium weed, of which, seven were sown at Injune and Mungallala in Queensland, Australia, with some species tested at both locations. At the Injune site, four introduced pasture species, i.e. Digitaria milanjiana, Clitoria ternatea, Cenchrus ciliaris and Chamaecrista rotundifolia significantly reduced shoot dry biomass of parthenium weed by 60 to 80%, while two native species, i.e. Bothriochloa macra and Eragrostis leptostachya had no significant effect. Cenchrus ciliaris and C. ternatea produced large amounts of dry fodder biomass, i.e. 404 and 360 g m −2, respectively. At the Mungallala site, three introduced species, i.e. D . milanjiana, Chloris gayana and C . rotundifolia and one native species, i.e. Dichanthium sericeum significantly reduced dry biomass of parthenium weed by >80%, producing sizeable fodder biomass (260 to 400 g m −2 ). The findings support the view that certain introduced and native pasture plant species can suppress the growth of parthenium weed at two contrasting locations and therefore show promise as potential tool for improved management of parthenium weed.